Physicochemical and antioxidant properties of Citrus macroptera peel pectin extracted by different methods and its impact on nutritional quality of strawberry jam during long-term storage - Robin Sarkar; Mukta Roy; Mahabub Alam; Animesh Sarkar; Abdullah A. Alarfaj; Sulaiman Ali Alharbi; Mohammad Javed Ansari (Discover Food)
Abstract This research explores the physicochemical properties and antioxidant activities of pectin derived from Citrus macroptera peel (CMP) by conventional heating extraction (CHE), microwave-assisted extraction (MAE) at various power levels (600 W-6 min, 450 W-12 min, 180 W-23 min), and ultrasonic-assisted extraction (UAE). MAE and UAE resulted in the highest pectin yields, with CHE producing the lowest. UAE achieved the highest equivalent weight, while MAE showed a significant reduction. Methoxyl content increased with MAE power levels, with the lowest in CHE. Anhydrouronic acid content exceeded 65% across all methods, indicating high pectin purity. Low methoxyl pectin (LMP, DE < 50%) was found in all methods except for MAE at 450 W, which produced high methoxyl pectin (HMP, DE > 50%). Functional properties, including water holding capacity (WHC), oil holding capacity (OHC), and swelling capacity (SC), varied across methods, with MAE-600 W showing superior performance. MAE-600 W, MAE-450 W enhance antioxidant activity, yielding higher TPC, TFC, and DPPH activity than CHE. The choice of extraction method had a significant impact on the quality of pectin, influencing its ability to preserve the nutritional value of strawberry jam over a 90-day storage period. Notably, pectin extracted using MAE-600 W, MAE-450 W, and UAE was most effective in maintaining both the quality and nutritional value of the strawberry jam, yielding particularly promising results. Graphical Abstract